2015
DOI: 10.3928/00220124-20150619-03
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Role for Nursing Education in Staff Nurse Participation in Antimicrobial Stewardship

Abstract: The role of the staff nurse in antimicrobial stewardship programs (ASPs) is not clearly defined. This study explored the ASP educational needs of staff nurses, using survey, focus group, and Delphi methods of engaging nurse educators. Low awareness of components of ASPs and areas of educational need were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 16 publications
0
32
0
3
Order By: Relevance
“…Our survey was based solely in an acute hospital setting so results cannot be easily compared with other surveys from across an acute and community/primary care work setting,11 or from other countries 12. We found only 25 (32%) of our staff rated their knowledge of antibiotics as ‘good’ or ‘very good’, similar to the proportion (36%) in a Scottish study 11.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our survey was based solely in an acute hospital setting so results cannot be easily compared with other surveys from across an acute and community/primary care work setting,11 or from other countries 12. We found only 25 (32%) of our staff rated their knowledge of antibiotics as ‘good’ or ‘very good’, similar to the proportion (36%) in a Scottish study 11.…”
Section: Discussionmentioning
confidence: 61%
“…Likewise, Olans and colleagues note that throughout the inpatient stay, the nurse is the central communicator among doctors, the pharmacy, the laboratory and discharge planner 12. The nurse is also a primary information source for patients and families, reinforcing and updating information from physicians, and providing education about medications and their appropriate use.…”
Section: Discussionmentioning
confidence: 99%
“…Through a survey of hospital-based nurse educators, Olans et al identified several educational needs, suggesting that addressing these would support nurses’ efforts to become active members of antimicrobial stewardship programs [22]. Our online course described here addressed some of these educational needs, including proper techniques for obtaining good culture samples, recognizing the difference between colonization and infection, awareness of signs and symptoms of infection and, most notably, improving confidence to ask prescribers about antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…Medical providers, for example, may resist interventions that they feel curtail professional autonomy and individualized care or may prescribe defensively to avoid litigation . Nurses have been less central in antibiotic stewardship in general, especially staff nurses, so they may not recognize their influential role in improving prescribing decisions and outcomes . Last, residents and their families may expect antibiotic treatment, which may serve as a barrier to antibiotic stewardship …”
mentioning
confidence: 99%